2D Perovskite Single Crystals for Photodetectors: From Macro‐ to Microscale. Issue 10 (26th July 2021) - Xu, Wenchao; Huang, Wenjun; Wu, Xiujia; Wei, Xiangfeng; Meng, Fancheng; Liu, Jiehua
Abstract : Lead‐halide‐based perovskite single crystals have attracted wide attention due to their excellent optical characteristics, photoelectric performance, and designable structures. 2D sheet‐like single‐crystal perovskite materials have several attractive characteristics, including larger exposed facets, adjustable thickness, good light absorption/transparency, and so on. However, single‐crystal perovskite sheets with a thinner thickness (<10 μm) are hard to obtain by conventional mechanical cutting due to the fragility of perovskite single crystals. Herein, the recent progress in research on 2D perovskite single crystals from macro‐ to microscale is reviewed. Crystal growth methods are classified into six strategies, including space‐limit method, surface‐tension method, top‐down method, spin‐coating method, solution‐phase method, and vapor‐phase method. Subsequently, the properties of 2D perovskite single crystals are further highlighted, such as optical properties, crystal defects, carrier transport properties, detection capability, and stability. Moreover, their applications in single‐crystal photodetectors are summarized. Finally, the summary and perspective on 2D perovskite single crystals are also briefly addressed. Abstract : 2D single‐crystal perovskites with excellent crystallinity, large exposed facets, and tunable thickness and bandgap enable great photoelectric properties and carrier transport abilities. Six methods to synthesize 2D perovskite crystals from macro‐ to microscale and their crystal properties are introduced. Then, the applications in single‐crystal‐based photodetectors are focused upon and a summary and a perspective on 2D perovskites are concisely provided.